Inhibiting adipose tissue M1 cytokine expression decreases DPP4 activity and insulin resistance in a type 2 diabetes mellitus mouse model. - Lee-Wei Chen (Public Library of Science (PLoS), 2021)
Adipose tissue inflammation is a major cause of the pathogenesis of obesity and comorbidities. To study the involvement of M1/M2 cytokine expression of adipose tissue in the regulatory mechanisms of dipeptidyl peptidase 4 (DPP4) and insulin resistance in diabetes, stromal vascular fractions (SVFs) were purified from inguinal adipose tissue of diabetic (Leprdb/db) and non-diabetic (Lepr+/+) mice followed by analysis of M1/M2 cytokine expression. SVFs of Leprdb/db mice exhibited increased TNF-α, IL-6, IL-1β, CCL2, and DPP4 mRNA expression but decreased IL-10 mRNA expression. Plasma from Leprdb/db mice induced TNF-α, IL-6, IL-1β, CCL2, and DPP4 mRNA expression and plasma from Lepr+/+ mice induced IL-10 mRNA expression in SVFs from Leprdb/db mice. Injection of Lepr+/+ plasma into the adipose tissue of Leprdb/db mice decreased mRNA expression of TNF-α, IL-6, IL-1β, CCL2, and DPP4 and protein expression of pJNK and DPP4 in SVFs, reduced mRNA expression of ICAM, FMO3, IL-1β, iNOS, TNF-α, IL-6, and DPP4 and protein expression of ICAM, FMO3, and DPP4 in liver, and suppressed mRNA expression of TNF-α, IL-6, IL-1β, and DPP4 in Kupffer cells. Plasma from Leprdb/db mice did not induce M1 cytokine expression in SVFs from Leprdb/db-Jnk1-/- mice. Altogether, we demonstrate that diabetes induces M1 but decreases M2 cytokine expression in adipose tissue. Diabetic plasma-induced M1 expression is potentially through pJNK signaling pathways. Non-diabetic plasma reverses M1/M2 cytokine expression, plasma CCL2 levels, DPP4 activity, and Kupffer cell activation in diabetes. Our results suggest M1/M2 cytokine expression in adipose tissue is critical in diabetes-induced DPP4 activity, liver inflammation, and insulin resistance.